Enhanced field-emission behavior of layered MoS2 sheets - Kashid, Ranjit V.; Late, Dattatray J.; Chou, Stanley S.; Huang, Yi-Kai; De, Mrinmoy; Joag, Dilip S.; More, Mahendra A.; Dravid, Vinayak P. (Small, 2013)
Field emission studies are reported for the first time on layered MoS2 sheets at the base pressure of approximate to 1 x 10(-8) mbar. The turn-on field required to draw a field emission current density of 10 A/cm(2) is found to be 3.5 V/m for MoS2 sheets. The turn-on values are found to be significantly lower than the reported MoS2 nanoflowers, graphene, and carbon nanotube-based field emitters due to the high field enhancement factor (approximate to 1138) associated with nanometric sharp edges of MoS2 sheet emitter surface. The emission current-time plots show good stability over a period of 3 h. Owing to the low turn-on field and planar (sheetlike) structure, the MoS2 could be utilized for future vacuum microelectronics/nanoelectronic and flat panel display applications.

Sensing behavior of atomically thin-layered MoS2 transistors - Late, Dattatray J.; Huang, Yi-Kai; Liu, Bin; Acharya, Jagaran; Shirodkar, Sharmila N.; Luo, Jiajun; Yan, Aiming; Charles, Daniel; Waghmare, Umesh V.; Dravid, Vinayak P.; Rao, C. N. R. (ACS Nano, 2013)
Most of recent research on layered chalcogenides is understandably focused on single atomic layers. However, it is unclear if single-layer units are the most ideal structures for enhanced gas solid interactions. To probe this issue further, we have prepared large-area MoS2 sheets ranging from single to multiple layers on 300 nm SiO2/Si substrates using the micromechanical exfoliation method. The thickness and layering of the sheets were identified by optical microscope, invoking recently reported specific optical color contrast, and further confirmed by AFM and Raman spectroscopy. The MoS2 transistors with different thicknesses were assessed for gas-sensing performances with exposure to NO2, NH3, and humidity in different conditions such as gate bias and light Irradiation. The results show that, compared to the single-layer counterpart, transistors of few MoS2 layers exhibit excellent sensitivity, recovery, and ability to be manipulated by gate bias and green light. Further, our ab initio DFT calculations on single-layer and bilayer MoS2 show that the charge transfer is the reason for the decrease in resistance in the presence of applied field.